Assessing knowledge sharing intention among academic staff in Faculty of Business and Management through personality traits / Norhidayah Mohd Rashid … [et al.] - Mohd Rashid, Norhidayah; Ma’amor, Hairunnisa; Badrolhisam, Nur Idayu; Md Mansor, Mohamad Naqiuddin (Faculty of Business and Management, Universiti Teknologi MARA, Shah Alam, Malaysia, 2019)
Technology is moving rapidly and educators have to keep up with this fast pace. Due to the pressure to embrace education revolution 4.0 introduced by the government of Malaysia, universities need to integrate technologies in teaching and learning sessions. To get the knowledge required, academicians need to attend training related. However, due to other commitments, knowledge sharing is the best option to gather the knowledge. Knowledge sharing has been accepted as a key dimension of effective knowledge management in an organization. However this situation is contradicting in education industry where every academician focus more on building their own image as the best academicians (Agyemang et al., 2016; Seonghee and Boryung, 2008). The researchers believe the level of willingness to share knowledge vary from one person to another depending on several factors including personality of individual. Thus, the purpose of this study is to identify how personality traits influence knowledge sharing attitude and behaviour among academic staff at Faculty of Business and Management, UiTM Selangor, Puncak Alam Campus. 169 sample of respondents will be collected by using convenience sampling technique. This study aims to contributes to the growing literature on the relationships between personality traits and knowledge sharing attitude and behaviour related to teaching and learning technologies (E-learning) among academicians in higher education.